On certain random polygons of large areas. (1998) - Kovalenko, Igor N.
Abstract : Consider the tesselation of a plane into convex random polygons determined by a unit intensity Poissonian line process. Let M ( A ) be the ergodic intensity of random polygons with areas exceeding a value A . A two-sided asymptotic bound exp − 2 A / π + c 0 A 1 6 < M ( A ) < exp − 2 A / π + c 1 A 1 6 is established for large A, where c 0 > 2.096, c 1 > 6.36 .